FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU WUS DALAM DETEKSI DINI KANKER SERVIKS METODE IVA DI WILAYAH PUSKESMAS MINASA UPA MAKASSAR - Andi Syintha Ida; Suriani B; Nurhadi Hatika Amin (Sekolah Tinggi Pariwisata Mataram, 2022)
Cervical cancer is one of the leading health problems striking women in the world According to the Global Cancer Statistics (2015) there are around 527,600 new cervical cancer cases and 265,700 deaths worldwide. The coverage of IVA examinations in Indonesia from 2008-2016 was 1,623,913 people. (4.34%) of the total target of 37.5 million Indonesian women. In 2015 IVA examination coverage was 1,268,333 people or (3.4%) to 1,925,943 people or around (5.2%) in 2016 While the target set for national screening was 50% in women aged 30-50 years within 5 years or until 2019. The purpose of the study was to determine the factors associated with WUS behavior by early detection of cervical cancer in the IVA method in the Minasa Upa Health Center Makassar area. The type of research was analytic survey with cross sectional design. The population and sample were women of childbearing age in the MinasaUpa Makassar Public Health Center area of ​​5031 people. The sampling technique was purposive sampling with a sample of 66 people. Data collection using questionnaires with Chi Square statistical tests. The study was conducted on the date of the research results that had a relationship with WUS behavior in early detection was knowledge (p = 00.0) Information exposure (p = 00,0) and variables that did not have a relationship were attitudes (0,53) so that health workers improve the IVA implementation program at WUS and increase the facilities and information facilities more effectively in counseling and counseling activities, recommending to families to support early detection. In order to consult with health workers about the implementation of the IVA program and improve insight and knowledge through access to information from various media.